Effect of preparation method of pyrolysis liquid mixed with coal on its ignition and combustion characteristics - Konstantin V. Slyusarsky; Askar Asilbekov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2024)
Relevance. The need to develop technological solutions to increase the competitiveness of pyrolysis processing of various wastes. Combustion of pyrolysis liquid in a mixture with coal is one of these solutions, which makes it possible to stabilize the properties of the obtained fuel and use in standard energy equipment. Aim. To determine the influence of the method of preparing a mixture of pyrolysis liquid and low-grade coal on its ignition and combustion characteristics, as well as on composition of the released gas-phase products, depending on the temperature of heating medium and concentration of the additive. Methods. Pyrolysis and oxidation characteristics were studied using thermogravimetric analysis, and formal kinetic constants were calculated using the Coates–Radfern method. Samples of mixed fuels were prepared by the methods of homogeneous mixing and surface wetting of pyrolysis liquid of rubber processing and low-grade coal. Ignition and combustion characteristics were determined using an experimental stand, and composition of gas-phase combustion products was determined using once-through gas analyzer. Results. The authors have determined the features of pyrolysis and oxidation of the pyrolysis liquid as well as the values of formal kinetics constants, indicating the physical nature of the factors that defining the rate of these processes. It was found that at 600 °C the ignition of the studied mixtures weakly depended on concentration of the additive, while at 700 and 800 °C the dependence was linear, and the differences between the samples prepared using different methods were insignificant. For samples obtained by the method of surface wetting, combustion of the additive occurred in the gas phase near the surface of the sample. For the samples obtained by the method of uniform mixing, it occurred predominantly in the bulk of the backfill. This led to more intense and complete coal combustion in these compositions due to more uniform releasing of heat and initiation of coal particles. The concentration curves of the NO, CO and CO2 release demonstrated, that behavior of the fuel mixture components was additive in terms of released gas-phase combustion products, as well as the absence of significant nonlinear effects over the entire studied range of temperatures and additive concentrations.